The Process of Determining an Auspicious Wedding Day in Watukebo Village, Banyuwangi, Within the Framework of Ethnomathematics - Andi Kurniawan; Rachmaniah Mirza Hariastuti; Dzurotul Mutimmah; Mufidatul Fauziyah (JURNAL PENDIDIKAN MATEMATIKA, 2026)
The purpose of this study was to explore ethnomathematics in the calculation of auspicious wedding days in Watukebo, Banyuwangi. The study was conducted within a qualitative framework with an ethnographic approach. The research area was chosen because it still applies Javanese calendar calculations for wedding traditions. The study involved three informants, purposively selected for their expertise. Data were triangulated through the collection method, participatory observation, and in-depth interviews, supplemented by documentation. Data were analysed qualitatively using the Miles and Huberman model. The results showed that determining auspicious wedding days in Watukebo, Banyuwangi, involves concepts of number operations, implication logic, number congruence, and modulo. These concepts can then be developed into contextual mathematics teaching materials that are expected to make learning more in-depth and meaningful. Keywords: calculation of good days, ethnomathematics, marriage